Organizational leaders’ personalities on employees’ job motivation in Malaysia - Wong, Wei Sern (2023)
The dark triad personality traits developed by Paulhus and Williams in 2002 consists of three different types of personality traits, which are Machiavellianism, Narcissism and Psychopathy. Machiavellianism is used to describe someone who is manipulative, cunning, and deceitful. Narcissism is used to describe a person who thinks they are better than others, someone who cannot take criticism and ignores the opinions of others. Psychopathy is used to describe someone who gets frustrated easily, insensitive and has a lack of remorse. Neuroticism which is one of the negative personality traits derived from the Goldberg Big-5 Personality Trait Model (1992) which describes someone who is low in self-confidence, gets anxious easily and moody. These dark triad and negative personality traits if possessed by an organizational leader will have negative consequences on an employee’s job motivation. This research investigates how an organizational leader’s dark triad and negative personality traits influences an employee’s job motivation in Malaysia. 216 participants are enrolled in this study and a questionnaire is given to measure their current organizational leader’s degree of possessing these dark triad and negative personality traits. Their job motivational levels depending on each of these personality traits are measured and the current prevalence rate of these dark triad and negative personality traits in Malaysia are also measured. The result of this study confirms that if an organizational leader in Malaysia possesses a high degree of any of these personality traits, the lower the job motivational levels will be for the employees in Malaysia. There is a negative relationship between these two variables. The prevalence rate measured in this research is 38% for Machiavellianism and Narcissism, 23% for Psychopathy and 25% for Neuroticism.